Roubini on global economic risks: “Dr Doom” or “Dr Realist”? - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2011)
Renowned as the brutally frank commentator that correctly predicted the 2008 financial crisis, New York University's economics professor Nouriel Roubini has made a reputation for himself as the prophet of doom. What does 'Doctor Doom' make of all the fuss about Asia's tiger and dragon economies? He shares his take at a lecture organised by SMU's Sim Kee Boon Institute for Financial Economics while informing audiences that he prefers to be known as 'Doctor Realist'.